Remediation of 137Cs radionuclide in nuclear waste effluents by polymer composite: adsorption kinetics, isotherms and gamma irradiation studies - Olatunji, Michael Adekunle; Khandaker, Mayeen Uddin; Mahmud, Habibun Nabi Muhammad Ekramul; Amin, Yusoff Mohd; Ademola, Janet Ayobami; Olorode, Deborah Oluwaseun (Springer Verlag, 2018)
Polypyrrole is incorporated with activated carbon in large size dopant solution and investigated for 137Cs removal studies. Adsorption experiments showed optimum conditions within 240 min contact time, pH 6, 0.2 g adsorbent and ≤ 100 mg/l adsorbate dose, respectively, while the kinetic data followed pseudo-first-order model. Isotherm data were reproducible by the Langmuir isotherm yielding 23 mg/g maximum sorption capacity. Regeneration of adsorbent was attempted and indicated promising results within three cycles. The surface behavior has also been examined and revealed a well-ordered structure under gamma irradiation. This is a cheap adsorbent to consider and has also proven to possess higher sorption capacity than most highly-cost inorganic materials in use.